BRANDING OMS (OPTIMALISASI MEDIA SOSIAL) SEBAGAI STRATEGI PENGUATAN NILAI KARAKTER, PRESTASI, DAN IDENTITAS SEKOLAH DI MAN 2 KLATEN - Rama Putra Gema Marulloh; Mohamad Joko Susilo (STKIP Pesisir Selatan, 2026)
This study aims to analyze and formulate the concept of Branding OMS (Social Media Optimization) as a strategy for strengthening character values, academic and non-academic achievements, and school identity at MAN 2 Klaten. The research focuses on developing a strong, credible, and sustainable digital identity that enables the madrasah to be easily recognized, remembered, and trusted by the public through systematic and consistent social media management. This study employed a qualitative approach using library research. Data were collected from relevant literature, including books and scholarly journal articles on school branding, character education, and digital communication, as well as institutional documents such as brand audit results and SWOT analysis of MAN 2 Klaten. Data analysis was conducted using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing and verification. The findings indicate that Branding OMS functions as a strategic instrument in representing Islamic character, discipline, and a culture of achievement through visual consistency, digital storytelling, and structured publication of achievements. Social media optimization is not merely a promotional tool but also serves as a medium for internalizing character values and strengthening school reputation.